Child domestic labour and mothers' employment in Turkey. Issue 1 (1st January 2016) - Susanli, Z. Bilgen; Inanc-Tuncer, Ozlem; Kologlugil, Serhat
Abstract: This paper takes an initial step in studying the determinants of child domestic labour and its relationship with mothers' employment in Turkey. We focus on children that are responsible for performing the domestic chores in their households. Using household level data from Demographic and Health Survey (2003), we find that the probability of child domestic labour is greater if the oldest child in the household is female; and this is stronger in rural areas. We also find that the likelihood of child domestic labour decreases with parental education. Our findings also suggest that the unobservable factors that increase the probability that a mother works increases the probability of child domestic labour in urban areas, but the opposite is true for rural areas.